Methodological Role of Mathematics to Estimate Human Blood Pressure Through Biosensors - R, Jegan; Hency Jose, P. Subha; Rajalakshmy, P.; Christu Raj, P. Anantha; Kanmani, Hannah Joice; Nimi, W. S. (International Journal of Integrated Engineering, 2021)
This paper presents a non-invasive technique and cuff less method for blood pressure measurement with a hardware prototype implementation. The sophisticated feature called pulse transit time (PTT) is extracted and investigated with a development of a smart system which consists of ECG, PPG sensor to estimate the systolic and diastolic blood pressure with support of advanced signal processing methodologies. The proposed method experiments have been carried out in hospital environment and tested with real time patients to validate the proposed method. The maximum error percentage of the proposed system has been shown to be 5.3% of systolic blood pressure (mmHg) and 4.7% of diastolic blood pressure (mmHg). This system also allows the monitoring of patient hypertension and overcome the limitation of cuff-based hospitalized measurement system.